TINJAUAN HUKUM PELAKSANAAN PENGAWASAN KANTOR URUSAN AGAMA TERHADAP PENGELOLAAN HARTA BENDA WAKAF: STUDI PADA KANTOR URUSAN AGAMA KECAMATAN MURHUM KOTA BAUBAU - Muskur La Ode Muhammad; Rizqan Moh (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2026)
The formulation of the problem proposed is How is the implementation of supervision of the Religious Affairs Office on the management of waqf assets at the Religious Affairs Office of Murhum District, What are the obstacles in implementing supervision of the Religious Affairs Office on the management of waqf assets at the Religious Affairs Office of Murhum District. This research is an empirical normative legal research. The data for this research were collected by means of document/library studies and interviews with competent parties at the Religious Affairs Office of Murhum District. Supervision of the management of waqf assets at the Religious Affairs Office (KUA) of Murhum District experiences various obstacles that affect the effectiveness of its implementation. This study examines important aspects in the implementation of supervision, including plans, instructions, targets, and policies, as well as basic principles such as supervisor independence and competencies that must be possessed. Through interviews with the Head of KUA, major obstacles were found such as limited human resources, unclear instructions, less measurable targets, challenges in policy enforcement, non-compliance of waqf managers, and minimal socialization to the community. This study recommends improving human resources, preparing clear procedures and guidelines, developing measurable performance indicators, and increasing socialization and counseling to the community and waqf managers. Thus, it is hoped that supervision of waqf asset management can run more effectively and provide optimal benefits to the community.This study recommends to the Murhum District Religious Affairs Officethat necessary to improve Human Resources by recruiting, Developing Performance Indicators, Intensive Socialization and Counseling, Increasing Independence and Supervisory Authority, Periodic Monitoring and Evaluation.